High-impact exercise promotes bone gain in well-trained female athletes - Taaffe, D. R.; Robinson, T. L.; Snow, C. M.; Marcus, R. (Journal of Bone and Mineral Research, 1997)
Maximizing peak bone mass, as well as reducing its loss after menopause, is important for the prevention of osteoporosis. One mode of activity, gymnastics training, invokes high impact loading strains on the skeleton which may have powerful osteogenic effects. To examine the role of athletic activity, specifically gymnastics, on bone mineral density (BMD) accretion, we monitored longitudinal changes in regional and whole body BMD in collegiate women gymnasts and competitive athletes whose skeletons are exposed to differential loading patterns: runners and swimmers. Two cohorts were studied. Cohort I = 26 gymnasts (19.7 +/- 1.2 years), 36 runners (21.1 +/- 2.7 years) and 14 nonathletic women (19.3 +/- 1.7 years) followed over an 8-month period. Cohort II = 8 gymnasts (18.9 +/- 1.1 years), 11 swimmers (20.0 +/- 2.3 years) and 11 nonathletic women (19.0 +/- 1.2 years) followed over a 12-month period. Lumbar spine (L2-4), femoral neck, and whole body BMD (g/cm2) were assessed by dual-energy X-ray absorptiometry. For cohort I, the percent change in lumbar spine BMD after 8 months was significantly greater (p = 0.0001) in the gymnasts (2.8 +/- 2.4%) than in the runners (-0.2 +/- 2.0%) or controls (0.7 +/- 1.3%). An increase in femoral neck BMD of 1.6 +/- 3.6% in gymnasts was also greater (p < 0.05) than runners (-1.2 +/- 3.0%) and approached significance compared with controls (-0.9 +/- 2.2%, p = 0.06). For cohort II, gymnasts gained 2.3 +/- 1.6% at the lumbar spine which differed significantly (p < 0.01) from changes in swimmers (-0.3 +/- 1.5%) and controls (-0.4 +/- 1.7%). Similarly, the change at the femoral neck was greater (p < 0.001) in gymnasts (5.0 +/- 3.4%) than swimmers (-0.6 +/- 2.8%) or controls (2.0 +/- 2.3%). The percent change in BMD at any site did not differ between eumenorrheic and irregularly menstruating athletes. These results indicate that bone mineral at clinically relevant sites, the lumbar spine and femoral neck, can respond dramatically to mechanical loading characteristic of gymnastics training in college-aged women. This occurred despite high initial BMD values and was independent of reproductive hormone status. The results provide evidence to support the view that high impact loading, rather than selection bias, underlies high BMD values characteristic of women gymnasts. Because all athletes underwent resistance training throughout the year of study, muscle strengthening activity did not appear to be a significant factor in the skeletal response observed in gymnasts. We conclude that activities resulting in high skeletal impacts may be particularly osteotropic for young women.